2013
DOI: 10.5897/ajmr12.1828
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and morphological variability of Sclerotinia sclerotiorum isolates of oilseed Brassica in India

Abstract: Sclerotinia stem rot caused by Sclerotinia sclerotiorum (Lib.) de Bary is one of the most serious disease and causes damage to oilseed Brassica. Seventeen geographical isolates of S. sclerotiorum from different geographical locations of India were compared for their growth under artificial culture conditions and the result was validated through random amplified polymorphic DNA (RAPD) markers. Based on the morphological studies, the isolates were grouped into fast growing (SR-01, SR-02, SR-05, SR-16) and interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…However, Contrary to the present observation, Kumar et al (2016) reported that HSR isolate had dirty white colony colour indicating the presence of two types at the same location for colony colour. Slight variations can occur for colony colour within isolates collected from different hosts as Sharma et al (2013) also found differences in colony colour among the isolates as whitish and dirty white, however, off white and grey white colony colour as observed by them were not found in any of the isolates in the present study. However, Ziman et al (1998) observed a slight variation in colony colour of S. sclerotiorum isolates collected from different hosts, which differentiate from white to brown but the white colour was predominant in most of the isolates.…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…However, Contrary to the present observation, Kumar et al (2016) reported that HSR isolate had dirty white colony colour indicating the presence of two types at the same location for colony colour. Slight variations can occur for colony colour within isolates collected from different hosts as Sharma et al (2013) also found differences in colony colour among the isolates as whitish and dirty white, however, off white and grey white colony colour as observed by them were not found in any of the isolates in the present study. However, Ziman et al (1998) observed a slight variation in colony colour of S. sclerotiorum isolates collected from different hosts, which differentiate from white to brown but the white colour was predominant in most of the isolates.…”
Section: Resultscontrasting
confidence: 42%
“…Choudhary and Prasad (2012) also observed two types of mycelial growth as fluffy and compact among different isolates. However, Sharma et al (2013) observed three types as scattered, smooth and fluffy mycelial growth among different isolates. The results of Kumar et al (2016) are in agreement with the present study as they have also examined this characteristic in nearly half of the isolates which we have taken afresh from different sites.…”
Section: Resultsmentioning
confidence: 99%
“…Mycelial bit touching the stem at 15 cm height was then secured by wrapping the parafilm strip around the stem. Wet cotton swab maintained high humidity during the infection period (Sharma et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, MCGs is another diversity analysis method based on the mycelial compatibility grouping (MCG) has been used in establishing the kinship among S. sclerotiorum isolates from chickpea (Kull et al, 2004; Li et al, 2008). In addition to it, the diversity based on the morphological appearance of sclerotia, mycelial growth, and ascospores formation have also been reported in analyzing the genetic diversity of S. sclerotiorum isolates in previous studies (Li et al, 2008; Sharma et al, 2013). However, polymorphism and genetic diversity of the S. sclerotiorum isolates at the morphological and DNA sequence level has not been comprehensively studied so far especially for the isolates from Brassica species of India.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation